2020
DOI: 10.1111/1541-4337.12633
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting flavor perception in space: Does the spacecraft environment influence food intake by astronauts?

Abstract: The intention to send a crewed mission to Mars involves a huge amount of planning to ensure a safe and successful mission. Providing adequate amounts of food for the crew is a major task, but 20 years of feeding astronauts on the International Space Station (ISS) have resulted in a good knowledge base. A crucial observation from the ISS is that astronauts typically consume only 80% of their daily calorie requirements when in space. This is despite daily exercise regimes that keep energy usage at very similar l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 230 publications
(354 reference statements)
0
24
0
Order By: Relevance
“…Flavor perception includes the integration of gustatory, olfactory, and trigeminal information 63 . Even though their afferents enter the CNS through different channels, these senses share distinct brain projection areas and integrative processing 40,64–66 . They mutually amplify each other and do not exhibit strong compensation for the impairment of other chemical senses, as is known for other senses such as vision and hearing 67 …”
Section: Complementary Hypothesis To Hypogeusia Related To Covid‐19mentioning
confidence: 99%
“…Flavor perception includes the integration of gustatory, olfactory, and trigeminal information 63 . Even though their afferents enter the CNS through different channels, these senses share distinct brain projection areas and integrative processing 40,64–66 . They mutually amplify each other and do not exhibit strong compensation for the impairment of other chemical senses, as is known for other senses such as vision and hearing 67 …”
Section: Complementary Hypothesis To Hypogeusia Related To Covid‐19mentioning
confidence: 99%
“…The starting point is not good, given that reports from astronauts describing space as smelling like: "gunpowder, hot metal, welding" (New York Hall of Science, 2016). The repeated recycling of limited air can potentially lead to the build-up of volatile pollutants (Taylor et al, 2019(Taylor et al, , 2020. At the same time, however, the lowered gravitational pull also leads to the build up of blood in the head, and this may constrict the nasal airways (NPR, 2012), leading to what is known as "space anosmia" (Varma et al, 2000).…”
Section: Future Travel: Space Tourismmentioning
confidence: 99%
“…This is what is sometimes referred to as dashboard dining or cup-holder cuisine (Hill, 2005 ; see also Morrison, 2021 , for one view of the future of dining in autonomous cars). Designed food experience for passengers on other forms of transport has also occupied the minds of many researchers' (e.g., Horwitz and Singley, 2004 ; Muecke, 2004 ; Spence, 2017a , b ; Taylor et al, 2019 , 2020 ). Returning to a theme that was mentioned earlier in this review, it has been suggested by de Syon ( 2008 ) that the provision of food on airplanes may also be one means of helping passengers to manage their anxiety (though more could certainly be done in this regard; e.g., Delahaye, 2017 ).…”
Section: Scent In Motion: the Multiple Roles Of Ambient Scent In Different Forms Of Transportmentioning
confidence: 99%
“…For chronic non-COVID-19 hyposmia a secondary gustatory impairment has been suggested [ 34 – 37 ]. As the processing of chemical information from olfaction, gustation, and trigeminal input uses overlapping brain regions and amplifies each other, a secondary hypogeusia could be explained through reduced amplification of gustation on a central nervous level [ 38 40 ]. Prolonged olfactory dysfunction after COVID-19 may also be associated with secondary hypogeusia as it has been shown for pre-COVID hyposmia of various etiologies [ 37 ].…”
Section: Discussionmentioning
confidence: 99%